2020
DOI: 10.1186/s12902-020-00608-2
|View full text |Cite
|
Sign up to set email alerts
|

Risk assessment for foot ulcers among Tunisian subjects with diabetes: a cross sectional outpatient study

Abstract: Background: Diabetic foot is an underestimated and redoubtable diabetes complication. The aims of our study were to assess diabetic foot ulcer risk factors according to International Working Group on the Diabetic Foot (IWGD F) classification, stratify patients into risk categories and identify factors associated with higher-risk grade. Methods: Cross-sectional setting over a period of 07 months, patients were randomly selected from the diabetic outpatients attending our unit of diabetology. Questionnaire and c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 34 publications
(97 reference statements)
1
10
3
Order By: Relevance
“…[8] Also our results are less than rates observed in Tunisia (39.6%). [6] Most of the patients in this study only 11.1% of all patients were regularly exercising which is noticeably lower that the reported rates in Benghazi in 2002 and in Sudan (41.5% and 27.7% respectively). [4,10] Less than two-thirds ie, 63.5% of all patients had diabetes eye screening within the previous years which is lower than the 2002 study (49.2%).…”
Section: Discussioncontrasting
confidence: 58%
See 3 more Smart Citations
“…[8] Also our results are less than rates observed in Tunisia (39.6%). [6] Most of the patients in this study only 11.1% of all patients were regularly exercising which is noticeably lower that the reported rates in Benghazi in 2002 and in Sudan (41.5% and 27.7% respectively). [4,10] Less than two-thirds ie, 63.5% of all patients had diabetes eye screening within the previous years which is lower than the 2002 study (49.2%).…”
Section: Discussioncontrasting
confidence: 58%
“…However, this may be attributed to the fact that 48.3% had never checked their blood pressure. [4] This result was nearer to what was observed in Tripoli (20.8%); [11] and lower than what was by Buzaid and Nagem, [8] and Zantour (6) et al, [6] respectively. Dyslipidemia was found in 42.1%, and only a minority had never checked their lipid profile; this is aremarkable improvement form the 2002 study when 76% had never checked their lipid profile.…”
Section: Discussionmentioning
confidence: 50%
See 2 more Smart Citations
“…Longer duration of diabetes was reported as a risk factor for diabetic foot by Shahi et al 21 Majority of participants were overweight (90%) and rest were obese in our study. Elevated BMI was associated with higher risk of developing diabetic foot in studies by Zantour et al and Sohn et al 22,23 However, Malgrange et al did not found this association. 24 The participants in our study had comorbidities like hypertension (80%), ischemic heart disease (64%) and hypercholesterolemia (72%).…”
Section: Discussionmentioning
confidence: 89%